Activity of nitrifying bacteria in aerobic granular sludge treating food industry wastewater - Paulo, Ana M. S. (2019)
Aerobic Granular Sludge (AGS) is an innovative wastewater biological treatment, which uses less energy and space compared to other technological solutions. AGS presents a diverse microbial community responsible for the simultaneous removal of carbon and nutrients. These communities are protected by extracellular polymeric substances (EPS), which provide a compact structure to the granules. As a result, bacteria present in the aerobic granules are more resistant to variable wastewater composition, as commonly produced in food industry. In this study, carbon and NH4+ removal from a fish canning plant wastewater was evaluated using an AGS-SBR (sequential batch reactor), operated during 90 days. Chemical oxygen demand (COD) at the outlet was below the discharge limit of 125 mg O2 L-1 throughout the operation. Nitrification occurred during the first 23 days of operation. Between days 24 and 60, nitrification was completely inhibited, without ammonium removal from the wastewater. Nitrifying bacteria recovered their activity right after a decrease in the wastewater organic load, showing that the inhibition of the nitrification process was reversible. This study will contribute to our knowledge on the application of the AGS process to food industry wastewater treatment.